2021
DOI: 10.1037/dev0001242
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal influence of parenting and parents’ traces on narrative identity in young adulthood.

Abstract: This longitudinal follow-up studied continued effects of parental influences on narrative identity in young adulthood. Decades of research have shown the importance of parental shared reminiscing and positive parenting for the development of children's and youths' autobiographical memory and narrative identity. Yet, research on long-term influences of parenting on narrative indices in adulthood is scarce, even though parents' traces remain a part of narrative identity throughout the life span (Köber & Habermas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…In a first step, caregiving figures can support adolescents in coping with their transforming identity by normalizing feelings of identity confusion, without dismissing them, and by underscoring their adaptive function as they essentially stimulate youngsters to explore new life paths and strive for personal identity ( 2 , 95 ). In addition, parents can potentially mitigate (or even prevent) identity issues in their children by providing them with a safe and (autonomy) supportive environment ( 96 ). Finally, should adolescents be challenged with persistent identity formation problems and be at risk of developing psychopathology, they should be able to receive psychotherapy that includes identity-specific modules prioritizing the treatment of problems related to self and identity.…”
Section: Discussionmentioning
confidence: 99%
“…In a first step, caregiving figures can support adolescents in coping with their transforming identity by normalizing feelings of identity confusion, without dismissing them, and by underscoring their adaptive function as they essentially stimulate youngsters to explore new life paths and strive for personal identity ( 2 , 95 ). In addition, parents can potentially mitigate (or even prevent) identity issues in their children by providing them with a safe and (autonomy) supportive environment ( 96 ). Finally, should adolescents be challenged with persistent identity formation problems and be at risk of developing psychopathology, they should be able to receive psychotherapy that includes identity-specific modules prioritizing the treatment of problems related to self and identity.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies indicate that characteristics of family relationships and parenting are associated with identity processes (Beyers & Goossens, 2008). Narrative research also indicates that parents have a special place in stories throughout life, IDENTITY TRAJECTORIES AND NARRATIVES because early memories are more likely to be integrated into the identity narrative and personal meaning-making (Camia et al, 2021). Given their prevalence in the narratives, family relationships were among the most important contexts for identity formation.…”
Section: Identity and Transition Related Themes In Identity Narrative...mentioning
confidence: 99%
“…For example, Dumas and colleagues (2009) documented a link between positive parenting in adolescence and greater narrative coherence in emerging adulthood. A recent longitudinal study found positive parental relationships together with a high parental presence in narratives predicted more coherent positive resolution in emerging adults’ life stories (Camia et al, 2021). Moreover, consistent with previous findings on gender differences in narrative identity (e.g., Grysman et al, 2016), females narrated more complex stories including multiple perspectives and elaborated emotional expressions compared to male stories (Camia et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A recent longitudinal study found positive parental relationships together with a high parental presence in narratives predicted more coherent positive resolution in emerging adults’ life stories (Camia et al, 2021). Moreover, consistent with previous findings on gender differences in narrative identity (e.g., Grysman et al, 2016), females narrated more complex stories including multiple perspectives and elaborated emotional expressions compared to male stories (Camia et al, 2021). These studies support the notion that narrative coherence in particular may in part develop as a function of parenting and other aspects of the family environment.…”
Section: Introductionmentioning
confidence: 99%